The effects of migration on the practice and perception Female Genital Cutting (FGC) among the Horn of Africa's immigrants in Melbourne Australia - Sadia Hassanen; Dawit Okubatsion Woldu; Rahma Mkuu (AIMS Press, 2019)
This research examines the effects of migration on the practice and perception of Female Genital Mutilation or Cutting (FGM/C) among Horn of Africa immigrants in Melbourne Australia. According to UN 2016 report, on (FGM/C), there are at least 200 million girls and women alive today globally that have undergone some of form of FGM/C. The same report highlights that most of these practices are concentrated in parts of Africa, Middle East and South Asia. Our research employed in-depth semi-structured interviews with 50 men and women informants and five focus groups among the Horn of Africa immigrants living in Melbourne Australia. Interview and focus group data were analysed using MAXQUDA text analysis software to see emerging themes from the data. Upon the examination of the interviews and focus group data, we found that gender and immigration were the two factors that influenced immigrant's perception about FGC. Understanding the social and cultural dynamics on the perception of FGC among immigrant communities in the West could help in devising appropriate interventions to tackle FGC in several groups where this practice is commonly occurring.